The 'Other' Woman in Contemporary Television Drama: Analyzing Intersectional Representation on Bones. - Meyer, Michaela (Sexuality & Culture, 2015)
This essay theorizes intersectional representation as a strategic device used in twenty-first century television narrative by examining the generically 'Other' woman in television drama. This character is often racially, ethnically, economically and sexually 'othered'. She appears on numerous broadcast television programs, and yet remains relatively invisible in cultural discourses of television. I offer a critical reading of the intersectional representation used on FOX's series Bones as a means of exposing how intersectional imagery functions to re-center identity politics on White, heteronormative, middle-class values. That these images remain largely invisible in academic discussions of race, ethnicity, sexuality and class on television while appearing frequently in the most economically successful television narratives speaks to the complexity of intersectional identity politics in contemporary media studies.